Теорія і практика формування професійної готовності майбутніх учителів до використання хмарних технологій у навчально-виховному процесі - Хміль, Наталія (My University, 2021)
У дисертації представлено цілісне й системне дослідження теоретичних засад і практичного розв’язання проблеми формування професійної готовності майбутніх учителів до використання хмарних технологій в освітньому процесі. На підставі аналізу наукової педагогічної літератури висвітлено стан дослідження проблеми формування професійної готовності майбутніх учителів до використання хмарних технологій в освітньому процесі. Репрезентовано зарубіжний досвід упровадження хмарних технологій в освітній процес та досвід професійної підготовки майбутніх учителів до їх застосування в освітньому процесі. Обґрунтовано методологічну стратегію наукового пошуку розв’язання досліджуваної проблеми. У роботі розкрито суть хмарних технологій, визначено їхню роль в освіті; розглянуто можливості їх використання в освітньому процесі закладів загальної середньої освіти та в професійній підготовці майбутніх учителів; обґрунтовано, що хмарні технології в освітньому процесі виконують різні функції, зокрема дидактичні, функції інтенсифікації освітнього процесу, функції організації навчальної діяльності та управління нею; запропоновано класифікацію хмарних сервісів за педагогічними можливостями, які вони реалізують в освітньому процесі; сформульовано визначення професійної готовності майбутніх учителів до використання хмарних технологій в освітньому процесі, визначено та схарактеризовано її структурні компоненти. Теоретично обґрунтовано педагогічну систему формування професійної готовності майбутніх учителів до використання хмарних технологій в освітньому процесі, визначено та розроблено компоненти системи (цільовий – мета, завдання, принципи; змістовий – зміст навчання; технологічний – методи, форми, засоби; суб’єкт-суб’єктний – суб’єкт (викладач ЗВО), об’єкт (здобувач вищої освіти, майбутній учитель); середовищний – хмаро орієнтоване навчально-інформаційне середовище для підготовки майбутніх учителів до використання хмарних технологій в освітньому процесі). Аналіз результатів експериментальної роботи підтвердив ефективність педагогічної системи формування професійної готовності майбутніх учителів до використання хмарних технологій в освітньому процесі в умовах закладу вищої освіти. The dissertation presents a holistic and systematic study of the theoretical foundations and practical solutions to the problem of forming the professional readiness of future teachers to use cloud technologies in the educational process. Based on the analysis of scientific-pedagogical literature, the state of the study of the problem of forming the professional readiness of future teachers for the use of cloud technologies in the educational process is disclosed. The foreign experience of introducing cloud technologies into the educational process and the experience of professional training of future teachers for their use in the educational process are presented. The methodological strategy of the scientific search for a solution to the problem under study has been substantiated. The work reveals the essence of cloud technologies, defines their role in education; the possibilities of their use in the educational process of institutions of general secondary education and in the professional training of future teachers are considered; it is substantiated the fact that cloud technologies in the educational process perform various functions, in particular, didactic ones, the functions of intensifying the educational process, the functions of organizing educational activities and managing them; the classification of cloud services according to the pedagogical capabilities that they implement in the educational process is proposed; the definition of the professional readiness of future teachers to use cloud technologies in the educational process is formulated, its structural components are identified and characterized. We understand the professional readiness of future teachers to use cloud technologies in the educational process as a personal state of the subject (future teacher), which encourages them to productive use of cloud technologies in the educational process, which is manifested by a positive attitude, interest, desire; possession of a set of theoretical knowledge, practical skills and abilities; developed the ability to self-assess their professional level and awareness of the need for further professional development in this activity. It is substantiated that the structure of professional readiness of future teachers to use cloud technologies in the educational process is represented by four components: motivational-valuable (characterized by motivational focus on the introduction of cloud technologies in the educational process), cognitive (determined by a set of general theoretical, psychological-pedagogical, methodological and information technology knowledge necessary for teachers to effectively use cloud technologies in the educational process), operational (characterized by a set of organizational, design, methodological, creative, information technology skills of interpersonal and group interaction of future teachers, they need to successfully use cloud technologies in the educational process) and reflexive-prognostic (manifested through the formation of students' analysis skills educational and cognitive activities, assess their knowledge, practical skills in order to further improve them in terms of organizing the educational process using cloud technologies). The pedagogical system of forming the professional readiness of future teachers for the use of cloud technologies in the educational process is theoretically substantiated the components of the system are identified and developed (target-related – goal, objectives, principles; content-related – the content of training; technological – methods, forms, means; subject-subject – subject (a higher education teacher), object (a student, a future teacher); environmental – a cloud-oriented educational and information environment for preparing future teachers for use cloud technologies in the educational process). The purpose of the pedagogical system was to improve the professional training of future teachers and the formation of their professional readiness in the direction of using cloud technologies in the educational process. Based on the use of diagnostic tools, the levels of formation of the professional readiness of future teachers for the use of cloud technologies are identified. The analysis of the results of the experimental work confirmed the effectiveness of the pedagogical system of forming the professional readiness of future teachers for the use of cloud technologies in the educational process in the conditions of a higher education institution.
Хміль Н. А. Теорія і практика формування професійної готовності майбутніх учителів до використання хмарних технологій у навчально-виховному процесі : дис. ... д-ра пед. наук : 13.00.04 / Хміль Наталія Анатоліївна ; Державний вищий навчальний заклад «Донбаський державний педагогічний університет». – Слов’янськ, 2021. – 634 с.
Keywords: професійна готовність, майбутні вчителі, професійна підготовка, хмарні технології, хмарні сервіси, освітній процес, педагогічна система формування професійної готовності майбутніх учителів до використання хмарних технологій в освітньому процесі; professional readiness, future teachers, professional training, cloud technologies, cloud services, educational process, pedagogical system, the formation of professional readiness of future teachers, using cloud technologies in the educational process